Strengthening Student Entrepreneurial Competencies through Mentoring in Developing Innovative Functional Beverages - Bunga Nur Anas Thasia; Adelia Putri Utami; Adira Kania Putri; Aulia Nur Rahma; Erja Radia Sumantri; Linda Dwi Astuti (GUYUB: Journal of Community Engagement, 2026)
Limited practical entrepreneurial experience and low innovation capacity among students remain challenges in student entrepreneurship programs. Furthermore, the utilization of local resources as a foundation for developing innovative products has not been optimally integrated into entrepreneurship education. Therefore, this community service activity aims to strengthen students’ entrepreneurial competencies through mentoring in the development of an innovative functional beverage based on local resources, namely Cendol Daun Katuk (CENDAKA). This activity involved five students participating in the student entrepreneurship program at Sebelas Maret University. The implementation stages included needs identification, product innovation training, mentoring for product development and production, as well as mentoring on online and offline marketing strategies. Evaluation was conducted through observations of the 5 student participants and a consumer response questionnaire involving 110 respondents using a Likert scale. The results of the activity show that students successfully developed an innovative product by integrating traditional cendol with katuk leaf extract (Sauropus androgynus) as both a natural colorant and a functional ingredient. The mentoring process also helped students understand product development, innovation practices, and marketing implementation in entrepreneurial activities. Consumer responses indicated a high level of acceptance, with satisfaction scores above 80% across all evaluated aspects. These findings suggest that mentoring-based entrepreneurial activities can support the development of students’ entrepreneurial competencies while promoting the utilization of local resources and sustainable product innovation. Therefore, this initiative contributes to strengthening entrepreneurship education and community-based economic development.